Development of Securities Market In Nepal - Subedi, Santosh (JMC Research Journal, 2022)
The research article is primarily based on development of securities market in Nepal with the aim to analyze the development of securities markets in Nepal. For the accomplishment of the objectives the required data were mainly gathered from secondary sources published by annual report of the Security Board Nepal, different books from library, periodicals, newspaper cuttings, company's magazines etc. From the study, it is found that the number of listed companies has almost been in increasing trend although the growth trend has decreased. This indicates that the NEPSE might have incorporated most of the institutions and thus there is slow growth in listing. Observing the company traded to listed ratios, it can be assumed that NEPSE should monitor the obstacles in the market that are preventing the listed companies to remain untraded.The economic prosperous of the country, the uplift in annual turnover of securities market is quite necessary. Although, the listed companies in NEPSE has been highly dominated by finance companies, the contribution of financial institutions in generating turnover is highest, and the market capitalization of other institutions, which comprises hydropower, promoter share, mutual fund, preference share and other is strongest.